Incentive Effects in the Demand for Health Care: A Bivariate Panel Count Data Estimation - Riphahn, Regina Therese; Wambach, Achim; Million, Andreas (Journal of Applied Econometrics, 2003)
This paper contributes in three dimensions to the literature on health care demand First it features the rst application of a bivariate random eects estimator in a count data setting to permit the ecient estimation of this type of model with panel data Second it provides an innovative test of adverse selection and conrms that high risk individuals are more likely to acquire supplemental add on insurance Third the esti mations yield that in accordance with the theory of moral hazard we observe a much lower frequency of doctor visits among the self employed and among mothers of small childr
WiSo-Import:2015-03-26:2663
Keywords: Asymmetric information demand for health services bivariate panel count data estimation